COMBINATION OF LYRIC AND EPIC IMAGE IN OMON MUTON'S WORK (Example of The Man in the Mirror) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the combination of lyrical and epic imagery in the novel "Man in the Mirror" by Omon Mukhtor, one of the most famous representatives of Uzbek novels of the independence period, as well as the author's unique poetic style, skillful use of poets in the work. goes